Implementation of the Circular of the Minister of Manpower Number M/HK.04/III/2020 at PT Gajah Tunggal Tbk - Don Gusti Rao; Hartanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research reviewing the implementation of the Circular Letter of the Minister of Manpower (SE Menaker) Number M/3/HK.04/III/2020 on Worker Protection and Business Continuity in the Framework of Prevention and Countermeasures of Covid-19 in PT Gajah Tunggal Tbk aims to find out the extent ofthe effectiveness of implementing the policy in the industry, especially in PT Gajah Tunggal Tbk. The Ministry of Manpower as one of the main stakeholders of the man power in Indonesia, confirming worker protection and also business continuity in the midst of a pandemic that is a global issue of employment problems. The research method used is qualitative deskripitf. The results of the study showed that the implementation of SE Menaker went well, as evidenced by the enthusiasm of the company and employees in raising mutual awareness for the realization of synergy of workers and companies during the pandemic, taking various preventive measures to prevent Covid-19 by following the government's advice, not to find unilateral job cutsorlayoffs. based on agreements, and pay cuts during pandemic times for both healthy workers, sufferers, and Covid-19 survivors.